Pigment epithelium-derived factor is an interleukin-6 antagonist in the RPE: Insight of structure-function relationships - Bernardo-Colón, Alexandra; Lerner, Miriam; Becerra, S. Patricia (Frontiers in Physiology, 2022)
Retinal and choroidal inflammatory lesions increase the levels of the pro-inflammatory cytokine interleukin-6 (IL-6). Pigment epithelium-derived factor (PEDF) has anti-inflammatory properties, but it is not known if it can prevent the production of IL-6 by the retinal pigment epithelium. To investigate the anti-inflammatory effects of PEDF in the RPE, we used human ARPE-19 cells stimulated with human recombinant tumor necrosis factor-alpha (TNF-α) to induce overexpression of the IL6 gene. We found that the viability of ARPE-19 cells decreased by 22% with TNF-α at 10 ng/mL, being drastically decreased at ≥50 ng/mL. TNF-α at 5 -100 ng/mL elevated the production and secretion of IL-6 protein, as measured by ELISA. To challenge the TNF-α-mediated stimulation of IL-6, we used recombinant human PEDF protein. PEDF at 100 nM recovered the TNF-α-mediated loss of cell viability and repressed IL-6 gene expression as determined by RT-PCR. PEDF at 10-100 nM attenuated the IL-6 protein secretion in a dose dependent fashion (IC50 = 65 nM), being abolished with 100 nM PEDF. To map the region that confers the IL-6 blocking effect to the PEDF polypeptide, we used chemically synthesized peptides designed from its biologically active domains, pro-death 34-mer, and pro-survival 44-mer and 17-mer[H105A], to challenge the IL-6 overproduction. The pro-survival peptides recovered the TNF-α-mediated cell viability loss, and inhibited IL-6 secretion, while the 34-mer did not have an effect, suggesting a role for the pro-survival domain in blocking TNF-α-mediated cell death and IL-6 stimulation. Our findings position PEDF as a novel antagonistic agent of IL-6 production in RPE cells, underscoring its use for the management of retinal disease-related inflammation.